Observed Usage Errors during Meaningful Use Stage 2 Safety-Enhanced Design Summative Testing. Issue 1 (June 2014) - Furlough, Caleb; Barnes, Janey; Mauney, Jennifer; Belk, Alisha; Blanchard, Laura; Brooks, Teri; Brown, Megan; Glasscock, Naomi; Gross, Merryl; Hunt, Ellie; Mehranian, Hasmik
This report presents data from summative usability tests conducted by User-View on behalf of multiple vendors as part of MU2 certification. The objective is to present findings related to performance metrics and use errors associated with each prioritized certification criteria, shine the light on EHR effectiveness, and contribute to ongoing discussions of EHR usability.